Investigation of attitudes towards their branches and sport orientation of different types of competitive - Suat Aybek; Aycen Aybek (ROL Spor Bilimleri Dergisi)
The aim of the study is to investigate the attitudes and sport orientations of martial artists in different sectors in relation to gender, age, education level and sport experience. In this sense, the Attitudes Towards Challenge Sports and Multidimensional Sportsmanship Orientation Scale” was used as a data collection tool in the study. The study group consisted of a total of 310 active athletes, 236 male and 74 female athletes who actively participated in competitions. SPSS 28.0 program was used for data analysis. The t-test for independent samples and the ANOVA -test were used to compare the variables. According to the results of the study, no significance was found in the gender variable in the attitude of martial artists towards their branches. However, a statistically significant difference was found in the dimension of “respect for rules and management” according to the gender variable. In the sub-dimension “Respect for the opponent”, significance was found in favor of female athletes. In the “sub-dimension “Ambition” of athletes in different age groups, a significant value was found between age groups. In this context, the present results show that there are significant differences between athletes of different age groups in some subdimensions. While significant differences were found between age groups in the sub-dimensions of “ambition” and “respect for opponent”, there were no significant differences between age groups in other sub-dimensions. These results suggest that age may have an influence on the characteristics of athletes’ sportsmanship orientation. At the same time, although it was found that different levels of education could affect athletes’ attitudes toward martial arts, it was also clear that there were differences among different levels of education on the subdimensions of “sportsmanship orientation.”